Caring for our patients - fact or legend - an economic view - S.B. Williamson (AOSIS, 1981)
The debate on economic aspects of health care is beset with the conflict of balancing supply and demand, of offering a less adequate service to all people, or a maximal service to relatively few. Somewhere along this continuum is an area of optimal service; providing a range of services which the country can afford, the point at which we can best cut our coat to fit our cloth.